If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40 + -5x + 7 = 0 Reorder the terms: 40 + 7 + -5x = 0 Combine like terms: 40 + 7 = 47 47 + -5x = 0 Solving 47 + -5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-47' to each side of the equation. 47 + -47 + -5x = 0 + -47 Combine like terms: 47 + -47 = 0 0 + -5x = 0 + -47 -5x = 0 + -47 Combine like terms: 0 + -47 = -47 -5x = -47 Divide each side by '-5'. x = 9.4 Simplifying x = 9.4
| 2w^2+5w+3=0 | | 4x+6=2(x+7) | | 2x^3-x^2-10x-7=0 | | -3(6-x)-3=x-4 | | 8(x+3)=8x+2x | | 9x-1=4x | | (9/2)/8=n/4 | | 14+3(y+4)-2y= | | (12a^3b^2-6a^2b-24ab^2)/(6ab) | | X^2+21=11x-3 | | x^2+y^2-10x+10y=0 | | 1/4(x-9)1/15(4x-1) | | x^2+y^2=124 | | log(2x+5)-log(x-4)=1 | | 36s-28s-63= | | 5-(3-x)=x | | 8-3x=20-5x | | 1/3(x-10)1/8(3x-1) | | 14+3(y+4)-2= | | 15-ln(4-x)=0 | | 1/3(x-4)1/8(3x-1) | | f(x)=2x^3-2 | | 1/2(x-90)1/3(2x-1) | | (100-110/10)/2 | | 1/2(x-9)1/3(2x-10 | | 5x*3(6-2)+7= | | 4x=5t(3/4) | | 7x+5=7(x+1) | | 12x+72x=21 | | 8x=10t(2/6) | | 9(x+6)+3=57 | | 5*3(6-2)=7 |